OP0224 A placebo-controlled phase II study of hyperimmune caprine serum as potential treatment for established diffuse cutaneous systemic sclerosis. (23rd January 2014) - Quillinan, N.; McIntosh, D.; Haq, S.; Denton, C.
Abstract : Objectives: Hyperimmune caprine (goat) serum prepared under GMP conditions has been used to treat a number of inflammatory or autoimmune diseases including chronic inflammatory demyelinating polyneuropathy. We have performed a study to explore safety and tolerability of hyperimmune caprine serum (AIMSPRO®) in established diffuse cutaneous systemic sclerosis (dcSSc). Potential measures of efficacy and markers of biological activity were also examined. Methods: A double blind parallel group placebo controlled clinical trial was performed under clinical trial authorisation from the UK MHRA and with institutional ethical approval. After informed consent 20 patients with established dcSSc of greater than 3 years duration were randomised to receive either active (n=10) or placebo formulation (n=10) by subcutaneous twice weekly injection over 26 weeks. Safety and tolerability were assessed by AE and SAE monitoring. Clinical endpoints (MRSS, HAQ-DI and SF-36) were compared between baseline and 26 weeks. Clinically meaningful change in MRSS was defined as greater than 4 skin score units and more than 20% change from baseline. Serum levels of vWF, PIIINP and sIL-2R were measured to assess vascular, fibrotic and immunological pathology. Exploratory serum biomarkers were also measured including MCP-1 (CCL-2) that has previously been associated with clinical severity in SSc. Results: There were no safety concerns during this study. Frequency of adverse events was not different between active and placebo treated patients; 154 AE occurred in those receiving placebo and 139 AE in the AIMSPRO® treated subjects. The commonest adverse event was minor injection site reaction occurring in 12 subjects. There were 6 SAE in 3 subjects in the placebo group and 4 SAE in 3 subjects receiving active treatment. No SAE was judged treatment-related. Mean (±SD) baseline MRSS for the trial cohort was 15.1±7.1, with no significant difference between active or placebo groups. Mean skin score fell by 1.4±4.7 units with active treatment but worsened by 2.1±6.4 units on placebo. This difference did not reach statistical significance (p=0.18, unpaired t-test). Responder analysis suggested clinically meaningful improvement in MRSS at 26 weeks occurred in 5 (50%) of actively treated patients compared with 1 (10%) in the control group. 2 subjects showed deterioration of MRSS in each treatment group. Mean±SD for HAQ-DI at baseline was 1.15±0.07 for active and 1.59±0.63 for placebo group and at 26 weeks was 1.24±0.98 for active and 1.56±0.55 for placebo. These changes were not statistically different (p=0.34). No other clinical endpoints changed significantly in either treatment group. There were no significant changes in vWF, sIL-2R or PIIINP but serum levels of MCP-1 (pg/ml) showed a reduction after AIMSPRO® (baseline 262.3±101.1, 202.4±132.0 at 26 weeks) compared with placebo (baseline 280.6±133.6, 325.8±225.9 at 26 weeks) with a trend of difference between cohorts (p=0.10, unpaired t-test). Conclusions: These results confirm the tolerability and safety of this novel biological agent in a complex multisystem autoimmune rheumatic disease. Although not powered to confirm efficacy, the improvement in MRSS observed in half of subjects receiving active treatment cases warrants further evaluation. Disclosure of Interest: N. Quillinan: None Declared, D. McIntosh Shareholder of: Daval International Ltd., Consultant for: Daval International Ltd., S. Haq Shareholder of: Daval International Ltd., C. Denton: None Declared